2015
DOI: 10.1007/8904_2015_515
|View full text |Cite
|
Sign up to set email alerts
|

LARS2 Variants Associated with Hydrops, Lactic Acidosis, Sideroblastic Anemia, and Multisystem Failure

Abstract: Pathogenic variants in mitochondrial aminoacyltRNA synthetases result in a broad range of mitochondrial respiratory chain disorders despite their shared role in mitochondrial protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…For example, mutations in mitochondrial ARS enzymes that cause recessive diseases can directly affect protein solubility [74] or impair mitochondrial protein translation [4,5,46,50,5659,63,7579], consistent with a loss-of-function effect. With respect to ARS mutations that cause dominant peripheral neuropathy, structural analyses have revealed that the majority of GARS mutations affect residues within the dimer interface [80].…”
Section: Models To Study the Mechanism Of Ars Mutations In Human Diseasementioning
confidence: 99%
“…For example, mutations in mitochondrial ARS enzymes that cause recessive diseases can directly affect protein solubility [74] or impair mitochondrial protein translation [4,5,46,50,5659,63,7579], consistent with a loss-of-function effect. With respect to ARS mutations that cause dominant peripheral neuropathy, structural analyses have revealed that the majority of GARS mutations affect residues within the dimer interface [80].…”
Section: Models To Study the Mechanism Of Ars Mutations In Human Diseasementioning
confidence: 99%
“…In a study of 35 multi-ethnic patients carrying a TMEM70 mutation, 35% manifested with renal disease in the form of RTA, hydronephrosis and acute or chronic renal failure (69). In a newborn girl with MIMODS due to a mutation in the LARS2 gene, encoding for a mitochondrial amino-acyl-tRNA synthetase, progressive renal failure was responsible for mortality 5 days after birth (70). In three children from the same consanguineous parents, antenatal skin oedema, hypotonia, cardiomyopathy and tubulopathy were attributed to mutations in the MRPS22 gene (71).…”
Section: Mdsmentioning
confidence: 99%
“…Somatic mutations in SF3B1 are found in ≥80% of patients, sometimes in combination with mutations in other genes, including JAK2V617F, ASXL1, DNMT3A, SETBP1 , and TET2 . Congenital SA is associated with mutations in nuclear genes involved in heme biosynthesis ( ALAS2 and SLC25A38 ), iron‐sulfur‐cluster biogenesis/transport ( ABCB7 and GLRX5 ), thiamine‐transport protein ( SLC19A1 ), structural subunits of the respiratory chain complex ( NDUFB11 ), and mitochondrial protein synthesis and chaperones ( PUS1, YARS2, LARS2 , and HSPA9 ) or with mutations in mitochondrial DNA ( MTATP6 , or large mtDNA deletions) involved in mitochondrial biogenesis …”
Section: Introductionmentioning
confidence: 99%